Satisfacción del cliente: Análisis crítico aplicado al Registro Civil, identificación y cedulación del cantón Babahoyo de la Provincia de Los Ríos durante el 2022 - Cevallos Ortega, Carlos Julio (2023)
This research presents the results of a study carried out in the Civil Registry of the Babahoyo canton of the province of Los Ríos, which is in charge of guaranteeing the right to identity of people and regulating and regulating the management and registration of facts and acts related to the marital status of people and their identification. Objective: Evaluate the satisfaction of the client who uses the services offered. Methodology: Theoretical methods will be used (analysis-synthesis, inductive-deductive and historical-logical); Empirical: (qualitative and quantitative), in addition to strategic models such as Situational Maps, SERVIQUAL, kANO, which will allow us to understand relevant facts and phenomena throughout the research process. Results indices that will lead to expose the relationship between institutionality and customer satisfaction, determining deficient institutional conditions; in addition to quality and deplorable satisfaction when correlating the perspective with the perception of the client. Conclusion: The strategic EFE, EFI indices, in addition to the quality and service dimensions generated from the proposed methodology, can promote new questions susceptible to future research to improve the quality of life of the user and the offer of services